INSTAGRAM USE TO ENHANCE ABILITY IN WRITING DESCRIPTIVE TEXTS - Soviyah Soviyah; Diana Rahayu Etikaningsih (Indonesian EFL Journal, 2018)
Technology is changing the world we live in. It affects the way people see, think, and learn their environment and communicate with others. In the educational field, there have been previous studies revealing the positive attitudes toward the use of mobile devices and applications. However, the empirical studies of the practice of how to use a specific mobile device and application effectively are done in a limited scale. Taking the experimental research method, this study investigated the effectiveness of the use of Instagram application on the students’ performance in writing descriptive texts. The main research question was centred around whether there was significant difference in the ability of writing descriptive text between students who were taught using Instagram and those who aren’t. Involving random sampling technique, this study involved 50 students of a private high school in Yogyakarta as the research sample.  The empirical data were collected through pre and post tests. The data were analyzed quantitatively applying t-test computation and descriptive analysis. Results of the study indicate that there is significant difference in students writing score between those taught using Instagram and those who aren’t. In conclusion, teaching students writing by using Instagram pictures are more effective than teaching without using Instagram pictures. In other words, the use of Instagram is effective in teaching writing descriptive texts.  Keywords: technology; Instagram; experimental research; writing descriptive text.